Implementasi Sistem Informasi Data Pelanggan Dengan Metode Soft System Methodology (SSM) - Suratman, Suratman; Sofa Sofiana (Ikatan Ahli Informatika Indonesia, 2025)
The rapid development of information technology has had a significant impact on various aspects of life, including the business world. One aspect affected is customer data management. Customer data is a valuable asset that can be utilized to improve services, optimize business processes, and support more informed decision-making. However, many laundry businesses, including Melia Laundry & DryCleaning BSD, still manage customer data manually using bookkeeping or spreadsheets. To address this issue, a web-based customer data management information system is needed that can help Melia Laundry & DryCleaning BSD manage customer data better. In developing this system, the Soft System Methodology (SSM) approach is used, which is a method suitable for solving complex and unstructured problems, such as customer data management in laundry businesses. Through this research, the developed customer data management information system can simplify recording, storing, and searching for customer data with more than 80% accuracy, and more structured reporting.